Pengaruh Pengetahuan, Tingkat Pendidikan, dan Pendapatan Terhadap Preferensi Nasabah Dalam Mengambil Keputusan Menjadi Nasabah Bank Konvensional - Sihombing, Priska; Abidin, Zaenal (PT. Riset Press International, 2024)
The purpose of this study is to analyze the influence of knowledge, education level, and income on customer preferences in making decisions to become Conventional Bank customers. The sample used was 50 customer respondents from PT. Bank Central Asia, Tbk. The data used in this study was obtained from the results of filling out questionnaires by respondents. The research method used in this study is quantitative. The results showed that: (1) there was an influence between knowledge and preferences with a significant value of 0.000 < 0.05; (2) there is an influence between education level and preference with a significant value of 0.044 < 0.05; (3) there is an effect between income and preference with a significant value of 0.016 < 0.05; and the results of the submission of the coefficient of determination showed an R square value of 0.708 which means that as many as 70.8% of variables are bound to preferences for independent variables, namely knowledge, education level, and income while other factors 29.2% are influenced by other factors that are not studied.